Customer experience and associated customer behaviour in end user devices and technologies (smartphones, mobile internet, mobile financial services). (2017) - Joshi, Sujata; Bhatia, Sanjay; Raikar, Kiran; Pall, Harmanpreet
This research paper proposes to establish the relationship between customer experience and customer behavioural intentions of churn, advocacy, cross-sell, up-sell and complaint for cellular service providers for end user devices and technologies like smartphones, mobile internet and mobile financial services. The method adopted incorporates various determinants across the customer lifecycle which are sufficient in defining customer experience holistically. A primary survey was conducted on 5, 231 respondents by means of a questionnaire along with personal interviews. Data was analysed using descriptive analysis as well as through statistical backing of logistic regression tests. Results indicate that there is a significant relationship between customer experience of smartphone users and mobile financial services users and their customer behavioural intentions of advocacy, churn, cross-sell, up-sell and complaints. The implications of this research can prove useful for cellular service providers in formulating their marketing strategy, cross-sell and up-sell strategy, churn management strategy and customer acquisition/retention strategy.